(untitled) (Research, Society and Development, 2024)
Introduction: According to the World Health Organization, obesity is one of the most serious health problems to be faced. There are many factors that cause obesity and among these factors may be sleep quality and changes in the circadian cycle. Objective: To carry out a literature review looking for relationships between obesity, sleep quality and circadian cycle. Methodology: Searches were carried out in the PubMed and Scielo databases, using the descriptors: obesity, sleep quality, circadian cycle, ghrelin, leptin and the association between them. Results: Many studies report the relationship between sleep impairment, changes in the circadian cycle and the influence of these changes on obesity. Discussion: Studies and research are still unable to efficiently prove the relationship and mechanisms that increase the risk of obesity in people with an altered circadian cycle and/or changes in sleep. Studies point to the regulation of hormones such as ghrelin and leptin, interference in food choices and willingness to perform physical activities. New research needs to be developed into these relationships, contributing to better monitoring and development of programs that contribute to reducing obesity rates in the population.